An amide hydrogen bond templated [1]rotaxane displaying a peptide motif – demonstrating an expedient route to synthetic mimics of lasso peptides. Issue 27 (29th June 2020) - Young, Matthew J.; Akien, Geoffrey R.; Evans, Nicholas H.
Abstract : The rapid synthesis and characterization of an amide hydrogen bond templated [1]rotaxane – demonstrating a potential pathway to synthetic analogues of lasso peptides. Abstract : The rapid synthesis of an amide hydrogen bond templated [1]rotaxane is reported – demonstrating a potential pathway to synthetic analogues of lasso peptides. The structures of the [1]rotaxane and its unthreaded isomer have been characterized by NMR spectroscopy and modelled using DFT calculations.